Archbishop Mečislovas Reinys: his Letters from the Vladimir Prison - Vasiliauskienė, Aldona (Genocidas ir rezistencija, 2005)
The article is devoted to the last period of Archbishop Reinys’ life (1947–1953), when he was arrested by the Soviet security on 12 June 1947, interrogated for half a year, held in the basement of the Vilnius KGB, sentenced to 8 years, and in the beginning of 1948 transported by a special convoy to the Vladimir prison. The Soviet prisons did not break the great spirit of this man. Here, too, he remained faithful to the ideals he preached, spreading the love of God by his example, caring for his cellmates, and loved ones in freedom. His letters are a testimony to this.